Dispersion-guided ablation in conjunction with circumferential pulmonary vein isolation is superior to stepwise ablation approach for persistent atrial fibrillation. (1st March 2019) - Lin, Rongjie; Zeng, Cong; Xu, Kai; Wu, Shaohui; Qin, Mu; Liu, Xu
Abstract: Background: Due to the lack of optimal ablation strategy, the success rate of persistent atrial fibrillation (AF) is still low. We hypothesize that a strategy that targeting pulmonary triggers and dispersion areas in atria improves prognosis of persistent AF. Methods: We prospectively enrolled 142 persistent AF patients admitted for catheter ablation. These patients were randomly assigned in a 1:1 ratio to ablation with circumferential pulmonary vein isolation (CPVI) + ablation of electrogram dispersion areas (71 patients, group A) or stepwise ablation strategy (71 patients, group B). Results: Procedural time and fluoroscopy time did not differ between group A and group B (204.6 ± 26.9 min vs 207.8 ± 26.3 min and 7.3 ± 1.3 min vs 7.1 ± 1.3 min, respectively, P > 0.05), however, radiofrequency delivery time in group A was significantly shorter than that in group B (70 ± 7.2 min vs 83.2 ± 9.1 min, P < 0.001). In total, 265 electrogram dispersion areas were identified in 67 patients, and the most prominent areas were roof, bottom, and inferoposterior wall. The rates of acute AF endpoint (including AF termination and AFCL elongation >30 ms) and termination in group A were significantly higher than that in group B (97.2% vs. 71.8% and 70.4% vs. 15.5%, respectively, P < 0.001). During a follow-up period of 204 ± 67 days, both AF-free and AF/AT-free survival in group A were significantly higher than that in group B (P = 0.012 and P = 0.014, respectively). Conclusion: Dispersion-guided ablation in conjunction with CPVI is efficient, personalized, and accurate for persistent AF. Highlights: This is the first time to clarify the electrogram dispersion-guided driver ablation in adjunctive to CPVI is an efficient approach for persistent AF. Our study further supports the notion that electrogram dispersion analyses can precisely locate drivers that sustained AF. Smaller left atrial volume, longer atrial fibrillation cycle length and a history of AF lasted no longer than a year can achieve better results.